Wealth and whiteness in Latin America - Hugo Cerón-Anaya (economic sociology. perspectives and conversations, 2023)
Is there such a thing as humble skin color? In her study of perceptions of the African diaspora among elementary school students in the city of Guadalajara, Mexico, doctoral student Marleys Meléndez Moré found that children who possessed a phenotype similar to that attributed to Africanness do not self-identify as members of this community in any sense. Instead, the students used the term 'humble color' to refer to their dark skin tone.
Keywords: 300